Systematic overview of soft materials as a novel frontier for MRI contrast agents. Issue 45 (21st July 2020) - Gallo, Enrico; Rosa, Elisabetta; Diaferia, Carlo; Rossi, Filomena; Tesauro, Diego; Accardo, Antonella
Abstract : Gd(iii )-nanostructurated Constrast Agents (CAs) for Magnetic Resonance Imaging (MRI) can be designed and developed by manipulating soft material, including fibers, hydrogels and nanogels, in the nanometer scale. Abstract : Magnetic resonance imaging (MRI) is a well-known diagnostic technique used to obtain high quality images in a non-invasive manner. In order to increase the contrast between normal and pathological regions in the human body, positive (T1) or negative (T2) contrast agents (CAs) are commonly intravenously administered. The most efficient class of T1-CAs are based on kinetically stable and thermodynamically inert gadolinium complexes. In the last two decades many novel macro- and supramolecular CAs have been proposed. These approaches have been optimized to increase the performance of the CAs in terms of the relaxivity values and to reduce the administered dose, decreasing the toxicity and giving better safety and pharmacokinetic profiles. The improved performances may also allow further information to be gained on the pathological and physiological state of the human body. The goal of this review is to report a systematic overview of the nanostructurated CAs obtained and developed by manipulating soft materials at the nanometer scale. Specifically, our attention is centered on recent examples of fibers, hydrogels and nanogel formulations, that seem particularly promising for overcoming the problematic issues that have recently pushed the European Medicines Agency (EMA) to withdraw linear CAs from the market.